Retrospective review of drug‐induced Stevens‐Johnson syndrome and toxic epidermal necrolysis cases at a pediatric tertiary care institution. Issue 3 (14th February 2020) - Sibbald, Cathryn; Putterman, Elana; Micheletti, Robert; Treat, James; Castelo‐Soccio, Leslie
Abstract: Background/Objectives: Stevens‐Johnson syndrome and toxic epidermal necrolysis represent important sources of potential mortality and morbidity in children. There is a need for more clinical data in this population to determine whether specific treatments preferentially improve outcomes. Methods: This was a single‐center retrospective review of children admitted with drug‐induced Stevens‐Johnson syndrome, toxic epidermal necrolysis or Stevens‐Johnson syndrome/toxic epidermal necrolysis overlap at a tertiary care pediatric institution in North America from 2008 to 2018. Patients without a dermatology assessment and diagnosis were excluded. Demographic, clinical, and treatment information were abstracted and reviewed for all included patients. Results: Sixteen patients were identified, 43% female (7/16), with a mean age at presentation of 10.4 ± 5.2 years. Antibiotics were implicated in 56.3% of patients (9/16) and anticonvulsants in 31.3% (5/16). Sulfamethoxazole‐trimethoprim was the triggering antibiotic in 31.3% of patients. The majority of patients were treated with intravenous immunoglobulin alone (50%, 8/16) or intravenous immunoglobulin with steroids (25%, 4/16). Etanercept was added to intravenous immunoglobulin and corticosteroid in a 2‐year‐old patient, resulting in clinical stabilization and halting of epidermolysis. No patients died. Clinical sequelae were noted in five patients, including ocular complications (n = 4), labial adhesions (n = 1), and persistent skin dyspigmentation (n = 3). Conclusions: Our results highlight that sulfamethoxazole‐trimethoprim is an important cause of Stevens‐Johnson syndrome‐toxic epidermal necrolysis in children. Mortality was reassuringly low, but ocular sequelae were an important cause of morbidity. More data are needed to help determine whether specific treatments including etanercept may provide mortality or morbidity benefit in pediatric populations.